CFD analysis of a realistic reduced-scale modeling equipped with axial jet fan. (May 2015) - Musto, Marilena; Rotondo, Giuseppe
Abstract: Typically, in the experimental scale road tunnel model, the air flow induced by ventilation system is provided by an external fan. In this paper, the authors have numerically simulated full and reduced-scale tunnel in order to evaluate the possibility to realize a reduced scale of a road tunnel model with a realistic ventilation system consisting of impulsive jet fans. In particular, two different types of longitudinal ventilation systems were considered, traditional and alternative. The last one was equipped with jet fans that have the inlet/outlet sections inclined at a fixed pitch angle ( α =6°) toward the tunnel floor. The jet fan was simulated as a simple momentum source that provides a pressure rise (pressure drop) across them as a function of the outflow air velocity. The analyzed tunnel consists in a 800 m one directional bore with circular cross section 5.05 m radius; the jet fans were installed at 5.67 m from the floor. Furthermore a burning Heavy Good Vehicle (HGV), placed at 450 m far away the tunnel entrance, was considered. To simulate numerically the burning vehicle, the species transport equation combustion model with Eddy-Dissipation-Concept (EDC) model was adopted. In order to create a reduced-scale model from a full scale, Froude method was applied to preserve geometrical, kinematical and dynamical similitude. Temperature and axial velocity profiles, in different tunnel sections for both considered models (full and scaled) and ventilation systems, were provided. The numerical results showed a good agreement for the both ventilation systems. Highlights: Scaling procedure for road tunnel equipped with realistic ventilation systems. Froude method was applied to preserve similitude. λ ≤20 (scale factor) reduction scale was applied.